Written Language Errors in Elementary School Students: A Psycholinguistic Analysis - M, Asia (Journal La Sociale, 2026)
This study examines the written language errors produced by elementary school students in Makassar City through a psycholinguistic and educational management lens, foregrounding how linguistic performance is shaped by systemic, organizational, and instructional structures. Using a qualitative descriptive design, the research analyzed students’ written texts, classroom observations, and interviews with teachers to uncover the types, patterns, and underlying sources of writing errors. Findings reveal four dominant categories of errors orthographic, morphological, syntactic, and semantic each reflecting not only developmental cognitive processes but also the influence of instructional fragmentation, inconsistent feedback mechanisms, and limited teacher expertise in psycholinguistic-responsive pedagogy. Teachers’ perspectives further demonstrate how large class sizes, insufficient resources, and culturally unresponsive management practices constrain effective writing instruction, ultimately reproducing recurring student errors. The study argues that these linguistic weaknesses are organizational products, not individual deficits, and must therefore be addressed through strategic school management interventions. The implications highlight the need for coherent literacy programs, capacity-building for teachers, improved feedback systems, and managerial alignment between curriculum design and classroom delivery. By situating children’s written errors within the broader structure of educational governance, this study contributes to both psycholinguistic scholarship and educational management research, offering a deeper understanding of how institutional practices shape literacy outcomes. The results underscore that improving student writing accuracy requires integrated systemic reform rather than isolated classroom-level adjustments.